Characteristics that modify the effect of small-quantity lipid-based nutrient supplementation on child anemia and micronutrient status: An individual participant data meta-analysis of randomized controlled trials - Wessells, K. Ryan; Arnold, Charles D.; Stewart, Christine P.; Prado, Elizabeth L.; Abbeddou, Souheila; Becquey, Elodie; Huybregts, Lieven; Leroy, Jef L. (American Society for Nutrition, 2021)
Background: Small-quantity lipid-based nutrient supplements (SQ-LNSs) have been shown to reduce the prevalence of child anemia and iron deficiency, but effects on other micronutrients are less well known. Identifying subgroups who benefit most from SQ-LNSs could support improved program design. Objectives: We aimed to identify study-level and individual-level modifiers of the effect of SQ-LNSs on child hemoglobin (Hb), anemia, and inflammation-adjusted micronutrient status outcomes. Methods: We conducted a 2-stage meta-analysis of individual participant data from 13 randomized controlled trials of SQ-LNSs provided to children 6–24 mo of age (n = 15,946). We generated study-specific and subgroup estimates of SQ-LNSs compared with control, and pooled the estimates using fixed-effects models. We used random-effects meta-regression to examine potential study-level effect modifiers. Results: SQ-LNS provision decreased the prevalence of anemia (Hb < 110 g/L) by 16% (relative reduction), iron deficiency (plasma ferritin < 12 µg/L) by 56%, and iron deficiency anemia (IDA; Hb < 110 g/L and plasma ferritin <12 µg/L) by 64%. We observed positive effects of SQ-LNSs on hematological and iron status outcomes within all subgroups of the study- and individual-level effect modifiers, but effects were larger in certain subgroups. For example, effects of SQ-LNSs on anemia and iron status were greater in trials that provided SQ-LNSs for >12 mo and provided 9 (as opposed to <9) mg Fe/d, and among later-born (than among first-born) children. There was no effect of SQ-LNSs on plasma zinc or retinol, but there was a 7% increase in plasma retinol-binding protein (RBP) and a 56% reduction in vitamin A deficiency (RBP < 0.70 µmol/L), with little evidence of effect modification by individual-level characteristics. Conclusions: SQ-LNSs can substantially reduce the prevalence of anemia, iron deficiency, and IDA among children across a range of individual, population, and study design characteristics. Policy-makers and program planners should consider SQ-LNSs within intervention packages to prevent anemia and iron deficiency. This trial was registered at www.crd.york.ac.uk/PROSPERO as CRD42020156663.